A review on the integration of radiative cooling and solar energy harvesting. (September 2021) - Ahmed, Salman; Li, Zhenpeng; Javed, Muhammad Shahzad; Ma, Tao
Abstract: With developments in material science and thermal engineering, radiative sky cooling has received renewed interest as it provides passive cooling energy during both day and night. Similarly, solar energy harvesting systems, such as photovoltaics, photovoltaic/thermal, and thermal collectors, have been used extensively to meet global energy demands. Integrating the individual systems into the combined solar energy–radiative cooling (SE–RC) system provides multifunctionality, increased operating time, and higher energy gains per unit area. From initial studies to the latest developments, this review has analyzed such integrated systems considering their module configurations, design techniques, applied materials, operating conditions, and performance results. Despite their impressive potential, these systems encounter challenges of low cooling power, stringent spectral requirements, and varying energy supply and demand. Recent progress made to address such challenges, potential solutions, and future research directions have also been discussed. Considering the global energy crisis and environmental issues, the cooling, heating, and electricity generated by SE–RC systems will be used in diverse applications like buildings and vehicles. Therefore, it is anticipated that this review will serve as a guide for integrating solar energy and radiative cooling, and will help identify patterns that are not evident from single studies so to further promote research in this domain. Graphical abstract: Image 1 Highlights: Analyzed the integration of radiative cooling and solar energy harvesting systems. Categorized the integrated systems according to different conditions and parameters. Discussed the current challenges, potential solutions, and future research directions.